Olfaction scaffolds the developing human from neonate to adolescent and beyond - Schaal, Benoist; Saxton, Tamsin K.; Loos, Helene; Soussignan, Robert; Durand, Karine (Philosophical Transactions of the Royal Society B-Biological Sciences, 2020)
The impact of the olfactory sense is regularly apparent across development. The fetus is bathed in amniotic fluid (AF) that conveys the mother's chemical ecology. Transnatal olfactory continuity between the odours of AF and milk assists in the transition to nursing. At the same time, odours emanating from the mammary areas provoke appetitive responses in newborns. Odours experienced from the mother's diet during breastfeeding, and from practices such as pre-mastication, may assist in the dietary transition at weaning. In parallel, infants are attracted to and recognize their mother's odours; later, children are able to recognize other kin and peers based on their odours. Familiar odours, such as those of the mother, regulate the child's emotions, and scaffold perception and learning through non-olfactory senses. During juvenility and adolescence, individuals become more sensitive to some bodily odours, while the timing of adolescence itself has been speculated to draw from the chemical ecology of the family unit. Odours learnt early in life and within the family niche continue to influence preferences as mate choice becomes relevant. Olfaction thus appears significant in turning on, sustaining and, in cases when mother odour is altered, disturbing adaptive reciprocity between offspring and carer during the multiple transitions of development between birth and adolescence. This article is part of the Theo Murphy meeting issue 'Olfactory communication in humans'.
CRIS-Team WoS Importer:2020-05-12